Model development of criteria for strengthening disease control in district level by using the concept of new public management - ประวันเตา, วิรัช; วรศรีหิรัญ, ภัทรเดช; ประภาดากุล, สุประวีณ์; ทองชุบ, วินัย; วิจิตร, วรรณา; ติดเทียน, อุษารัตน์ (Disease Control Journal, 2018)
This research aimed to develop a model based on strongly sustainable disease control by using the concept of new public management. This was a research and development (R & D), mixed (mixed method) research. The research had two phases: (1) to create and verify model based on strongly sustainable disease control by using the concept of new public management, study documents of problems, concepts, theories, components, criteria requirements, In-depth interviews were provided to 5 experts and 81 district administrators in the second health zone, create criteria form for the focus group and the connoisseurship then examined the criteria and empirical data by using a questionnaire that had been tested for validity and reliability. Two hundred and two samples were arked and analyzed by using confirmatory factor analysis. (2) to implement and evaluate the criteria for development of the model based on strongly sustainable disease control by using the concept of new public management, the NPM-DC program was developed and distributed to five target districts, the research team supports follow-up counseling in self-evaluation, subsequently, 21 target district officers presented results of their implementation and self-assessment. The questionnaire was used to analyze the data by using descriptive statistics. The results showed that [1] the results of the modeling of the district's strongly disease control model based on the concept of the new state management consisted of 8 categories, including: (1) Executive district leadership (2) Strategic planning (3) Focusing on the public service (4) Measurement and analysis of data and information (5) Knowledge management and innovation (6) Development of human resources (7) Development of operational processes (8) Results of operations, that were 44 sub-elements. The results of the audit showed constructive validity in harmony with the empirical data at 0.05 level of the statistical significance, and [2] the results showed that the 5 target districts can use self-assessment data with empirical data effectively. The total score was 325-586 points (full 1,000 points). The total score was classified as the following: (1) process of works (categories 1-7) 270-371 points (full 600 points), the results (categories 8) 55-217 points (full 400 points) and the feasibility and usefulness 3.76-4.52 points and 3.95-4.71 points (full 5 points) and very-most level are possible. In conclusion, it is appropriate, useful, and possible practice for disease control in the district. Recommendations should be used as a tool to drive the disease control activities for the development of the District Quality of Life.